Magnum Beneficium est Pax, sed Dei Veri Beneficium est (ciu., 3.9). Augustine's Realism, Strategy, and Insight into Human Motives as a Prelude to Peace at all Levels of Human Existence - van Geest, Paul (Editorial Uniagustiniana, 2019)
The objective of this study is to examine the vision Augustine developed on the relationship between religion and politics, and how he conceived the Christian religion as the foundation of political and social action. Firstly, he emphasizes in his reflections on officials in the res publica that their work was marked by tragedy. State institutions and political relationships are characterized by the volatility and temporality. The only ones that do not seem to realize this are the politicians themselves, because the nature of their work does not contribute to the development of the ability to (self-) introspection and growth in humilitas (humility). Secondly, in his De Civitate Dei Augustine strove to present human history as a mirror in which each leader can see the impact of his own inner motives. The struggle between Jerusalem and Babylon, greed and generosity, sincerity and opportunism is a battle in the interior for Augustine. But in Book XIX of De civitate Dei Augustine finally also relates physical balance, irrational and rational motives, striving for integrity, the role of family and government, in order to show that inner peace and peace in any social context are interwoven.